Sistema de Matriarcado nos Arquipelagos dos Bijagos - Tubento, Medilanda Eliseu Amos (2023)
The dissertation refers to the matriarchy system in the Bijagó ethnic group and aims to understand how the system is established in the culture of the Bijagós in contemporary times. The aim of walking in this understanding led to the search to understand the constitution of kinship relationships based on matrilineality in this society. Thus, to portray, specifically, the formation of the identity and the experience of Ovtdé (man) and Okanto (woman) in the Bijagós islands. “Mama África”, the African continent personified in the figure of a mother: matriarchy as one of the social substrates of the peoples that inhabit the African continent. As we can see in Scholl's statement (2019; p.155): “This discourse is familiar to us when talking about Africa as a producer of common historical development, something disrupted by colonization, slavery and the diaspora”. Guinea-Bissau does not escape this phenomenon, since the country is famous for its ethnic pluralities, which ends up forming a web of different cultures, namely: habits, values and customs. The choice of method for carrying out has its methodological basis in the research of interdisciplinarity based on bibliographical references, oral tradition and linguistics. Its use is due to the fact that, in order to understand a phenomenon in the African context, it is essential to have several views, or a multifaceted perspective that leads to a better understanding of this phenomenon. The Africanization of the knowledge of the Bijagós includes its oral transmission from generation to generation, since in African reality the tradition of orality is predominant. The dissertation is divided into four chapters. In the first chapter “The methodological issues, which describe how the research was carried out, it presents the subjects, the field, the methods used and the trajectories made during the field work. For studies in the African context cannot take place in the fragmentation of disciplines. If in the case of the history of Africa, specifically south of the Sahara where it is characterized by the relative poverty of written sources, before the 16th century and the 7th century of the Christian Era, then other sources available for research are used, such as orality, (Ki-Zerbo, (2010, p.387). Like oral tradition and its methodology, living tradition and African knowledge (VANSIMA, 2010; HAMPATE BA, 2010; HOUNTUNDJI, 2008). Then, in the second chapter there is the contextualization of the bijagós of the archipelago, the origin, the people and the myth of creation. Continuing in the third chapter, the constitution of kinship relations in the matriarchal system based on matriliny is described, bringing elements of age group, marriage and family, and the last chapter, the analysis of the identity of Ovtdé (man) and Okanto (woman) in Bijagó society. constituent elements of the system, some with more tenacity, others in disuse. Some examples of this tradition would be the relationship between the matriarchy system and matriliny through the categories of the importance of the predominance of the age group as a relevant way of organizing society. The way of carrying out the marriage that preserves the female preponderance and its connection with the maternal uncle, the obligation to follow the customs established for the performance of the act. The family continues to be a primordial element to maintain matrilineality, through the uterine connection, the mother's “djorson”. The configuration of these aspects is based on the identity of Ojoco, a guest of the earth, whose life is given by Nindo-Deus (Supreme Being) and seeks a becoming, by reaching it he seeks to maintain and live with this conduct.